No efficacy of annual gynaecological screening in BRCA1/2 mutation carriers; an observational follow-up study - Hermsen, B B J (Nature Publishing Group, 2007)
BRCA1/2 mutation carriers are offered gynaecological screening with the intention to reduce mortality by detecting ovarian cancer at an early stage. We examined compliance and efficacy of gynaecological screening in BRCA1/2 mutation carriers. In this multicentre, observational, follow-up study we examined medical record data of a consecutive series of 888 BRCA1/2 mutation carriers who started annual screening with transvaginal ultrasonography and serum CA125 between 1993 and 2005. The women were annually screened for 75% of their total period of follow-up. Compliance decreased with longer follow-up. Five of the 10 incident cancers were interval tumours, diagnosed in women with a normal screening result within 3–10 months before diagnosis. No difference in stage distribution between incident screen-detected and interval tumours was found. Eight of the 10 incident cancers were stage III/IV (80%). Cancers diagnosed in unscreened family members had a similar stage distribution (77% in stage III/IV). The observed number of cases detected during screening was not significantly higher than expected (Standardized Incidence Ratio (SIR): 1.5, 95% confidence interval: 0.7–2.8). For the subgroup that was fully compliant to annual screening, a similar SIR was found (1.6, 95% confidence interval: 0.5–3.6). Despite annual gynaecological screening, a high proportion of ovarian cancers in BRCA1/2 carriers are interval cancers and the large majority of all cancers are diagnosed in advanced stages. Therefore, it is unlikely that annual screening will reduce mortality from ovarian cancer in BRCA1/2 mutation carriers.